The smear layer created by scaling and root planing is physiologically eliminated in a biphasic process - Fernanda Regina Godoy ROCHA; Daniela Leal ZANDIM-BARCELOS; Carlos ROSSA JUNIOR; José Eduardo Cezar SAMPAIO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Mechanical instrumentation of the root surface causes the formation of a smear layer, which is a physical barrier that can affect periodontal regeneration. Although different procedures have been proposed to remove the smear layer, there is no information concerning how long the smear layer persists on root surfaces after instrumentation in vivo. This study assessed the presence of the smear layer on root surfaces over a 28-day period after subgingival instrumentation with hand instruments. Fifty human teeth that were referred for extraction because of advanced periodontal disease were scaled and root planed (SRP) by a single experienced operator. Ten teeth were randomly assigned to be extracted 7, 14, 21, and 28 days after SRP. Another 10 teeth were extracted immediately after instrumentation (Day 0, control group). The subgingival area of the instrumented roots was evaluated with scanning electron microscopy. Representative photomicrographs were assessed by a blinded and calibrated examiner according to a scoring system. A rapid and significant (p < 0.05, Z test) initial reduction in the amount of smear layer was observed at 7 days, and a further significant (p < 0.05) decrease was observed 28 days after SRP. Interestingly, even 28 days after SRP, the smear layer was still present on root surfaces. This study showed that the physiological elimination of the smear layer occurred in a biphasic manner: a rapid initial reduction was observed 7 days after instrumentation, which was followed by a slow process leading to a significant decrease 28 days after instrumentation.